Comparative screening study on the adsorption of Aqueous Pb(II) using different metabolically inhibited bacterial cultures from industry - Brink, Hendrik Gideon (University of Pretoria, 2023)
Dissertation (MSc (Environmental Technology)) -- University of Pretoria, 2023.